If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(x + 3) = 4a + 8 Reorder the terms: a(3 + x) = 4a + 8 (3 * a + x * a) = 4a + 8 (3a + ax) = 4a + 8 Reorder the terms: 3a + ax = 8 + 4a Solving 3a + ax = 8 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 3a + -4a + ax = 8 + 4a + -4a Combine like terms: 3a + -4a = -1a -1a + ax = 8 + 4a + -4a Combine like terms: 4a + -4a = 0 -1a + ax = 8 + 0 -1a + ax = 8 Reorder the terms: -8 + -1a + ax = 8 + -8 Combine like terms: 8 + -8 = 0 -8 + -1a + ax = 0 The solution to this equation could not be determined.
| 3x^3+12x^2+18x= | | 3x+42+40-4x=0 | | -5x+7(-2x-23)=-47 | | -3.17=x-9.48 | | 5t+1=3t-1 | | 2x+a=6x-b | | 43-3x=6x+22 | | 3x-9=3x+7 | | 11-10x=107-31x | | 131-6x=30x+15 | | [x-7]=8 | | Y+3.17=2.1 | | 4r+2r=3r-6 | | 36x+48-10x+25=6x-27 | | Ix-1I=7 | | 16k-1=k+14 | | -7y-35= | | -108-10x=8x | | 4x=(-36) | | 6(x+7)=4x+2x+9 | | 37-2(2x+1)=30-2x | | 2t+6=3t-7 | | .8+3z=.5z+1 | | 3x^2-3x+6=0 | | -6X=38 | | 5k+k=k+14 | | 9x+9=9(x+7)-9 | | 3x+14=51-10x | | 188-5x=6x+23 | | -2-6(y+5)=45 | | 30=42y+18 | | (2-5)(7+a)+15=3 |